Expression and Significance of MyD88 in Patients With Gastric Cardia Cancer in a High-Incidence Area of China - Chen, Jingyao; Xia, Di; Xu, Muming; Su, Ruibing; Lin, Wenting; Guo, Dan; Chen, Guangcan; Liu, Shuhui (Frontiers in Oncology, 2020)
Background: Gastric cardia cancer (GCC) arises in the area of the stomach adjoining the oesophageal-gastric junction and has unique risk factors. It was suggested that Helicobacter pylori (H. pylori) infection is associated with GCC from high-risk population. Myeloid differentiation factor 88 (MyD88) is a crucial adaptor molecule in toll-like signalling pathway recognizing H. pylori. Its role in GCC has not been recognized yet. In this study, we aim to investigate the expression and significance of myeloid differentiation factor 88 (MyD88) in gastric cardia cancer tissue. Methods: Expression of MyD88, NF-κB p105/p50 and infection of helicobacter pylori was detected by immunohistochemistry in gastric cardia tissue. The correlation of MyD88 expression to NF-κB p105/p50 expression, helicobacter pylori infection and clinicopathologic characteristics in gastric cardia tissue was analyzed. The involvement of MyD88 in patient prognosis was also analyzed. Results: We found a statistically significant trend for progressive increase of MyD88 expression from normal mucosa to inflammation (p=0.032) and higher expression of MyD88 in GCC tissues in comparison with non-malignant cardia mucosa (p=0.007). Particularly, high expression of MyD88 was found in intestinal-type adenocarcinoma with inflammation. Patients with high MyD88 staining revealed a better differentiation(p=0.041). MyD88 also positive correlated with NF-κB p105/p50 expression(p=0.012) in cancer tissue. Expression of MyD88 was increased but not significantly in biopsies with H. pylori infection compared with noninfected biopsies. Multivariate analyses revealed lymph node metastasis but not MyD88 expression was an independent predictor for patient survival. Conclusion: These findings provide pathological evidence that upregulating MyD88 and inducing inﬂammation might involve in gastric cardia carcinogenesis in high risk population.